Designing appropriate English learning materials for Nautical Department at Politeknik Ilmu Pelayaran Semarang - F Fatimah; Irma Shinta Dewi; Sri Purwantini (University of Muhammadiyah Purwokerto, 2020)
This research is aimed to find out the target and learning needs of Nautical students at PIP Semarang and designing the appropriate material for Nautical students at PIP Semarang. This is a Research and Development project. The steps of doing this research are (1) need analysis (2) make syllabus (3) designing materials (4) expert consultation (5) try out material (6) evaluation. The subject of this research is the third-semester students of Nautical department at PIP Semarang. The instruments used are questionnaires for need analysis, interview guide and observation sheets. The data were analyzed by using descriptive quantitative and qualitative. The results of the research recommend three units namely (1) Initial Call (2) Message Marker and (3) On Board Communication Phrases which are developed with communicative approach. The research gives contribution to the teaching and learning English at Nautical Department of Politeknik Ilmu Pelayaran Semarang.